A low-cost mitigation system for ammonia removal from broiler house exhaust air - Jingjing Luo; Jinsheng Rong; Shizhen Zhou; Haoliang Wang; Miao Li; Xiliang Yan; Yingbao Wu; Yan Wang (Poultry Science)
Most chicken farms in China utilize chemical deodorants in conjunction with a screen positioned near the fan outlet at the end of the breeding house for deodorization. However, practical observations indicate that the placement of these screens can impact ventilation and animal growth, while the efficacy of chemical deodorants remains uncertain. In this study, we utilized computational fluid dynamics (CFD) simulations to model a broiler house and analyzed airflow patterns at varying screen distances to assess their effect on indoor ventilation. Additionally, we designed an environmental simulation chamber to evaluate chemical deodorants. Subsequently, we developed an economical and effective ammonia removal blocking system (ARBS). The CFD simulation results show that the simulated wind speeds closely matched measured values, with errors within acceptable ranges. In the experimental chicken house, positioning the screen 3.5 meters from the fan outlet can optimize airflow and is the optimal placement. The results of the environmental simulation chamber show that 80 ppm hypochlorous acid and 70 ppm chlorine dioxide are cost-effective, achieving high ammonia (NH₃) removal rates. Field validation in a broiler house demonstrated that using 80 ppm hypochlorous acid with the ARBS achieved NH₃ and dust removal efficiencies of 82 % and 77 %, respectively. The ARBS requires an initial investment of $1,900 and has an annual operating cost of $590. This system effectively reduces NH₃ emissions with less investment, and its installation can be optimized via CFD simulations to avoid adverse effects on poultry. Therefore, the ARBS presents a viable solution to address NH₃ challenges in poultry production.